ДЕЙСТВИЕ НИЗКОТЕМПЕРАТУРНОГО СТРЕССА НА ИЗОПЕРОКСИДАЗЫ ПШЕНИЦЫ, РАЗЛИЧАЮЩИЕСЯ ПО ИЗОЭЛЕКТРИЧЕСКИМ ТОЧКАМ (Experimental biology, 2017)
Wheat seedlings responded to low temperatures with specific activity changes in peroxidase izoenzymes differing in isoelectric points. With the use of cluster analysis, similarities and differences between the wheat genotypes were evaluated by total, relative and specific activity in multiple peroxidase forms separated by isoelectric focusing.
Keywords: peroxidase; wheat genotypes